Effect of Omega-3 and Multivitamins on Aluminum-Induced Changes in Serum and Tissue Enzyme Activities in Rats - HABBIB, OMAR A.M.AL.; SULAIVANY, BASIM S.A.AL. (Science Journal of University of Zakho, 2013)
The present work was designed to study the effect of omega-3 and multivitamins on aluminum-induced changes in some tissue enzymes level in male albino rats. For the present work, seventy adult male rats were randomly divided into seven groups; fed on normal diet and treated as follows: Control group 1supplied with tap water. Group 2 supplied with 0.2 ml/rat of the vehicle (oil ). Group 3 supplied orally with 0.2 ml/rat aluminum solution. Group 4 supplied orally with 0.2 ml/rat aluminum solution and diluted acetic acid solution (0.5 %). Group 5 supplied orally with 0.2 ml/rat aluminum solution and omega-3. Group 6 supplied orally with 0.2 ml/rat aluminum solution and multivitamins. Group 7 supplied orally with 0.2 ml/rat aluminum solution and both antioxidants, omega-3 and multivitamins. After treating the animals with the tested materials daily for 30 days, the activities of serum alkaline Phosphatase (ALP), acid Phosphatase (ACP), Alanine Transaminase (ALT) and Aspartate Transaminase (AST) were increased while their activities in liver and brain tissues were significantly decreased. The toxicity of Aluminum was enhanced in the presence of acid as indicated by further changes in the levels of above parameters as compared with those of Al treated animals. The toxic effect of Al, in the presence of antioxidants such as omega-3 and multivitamins, was comparatively reduced and the studied parameters showed tendencies to change toward the normal levels. Thus, animals treated with Al in the presence of above antioxidants showed slight decreases in the activities of tissues ALP, ACP, ALT and AST. From the results of the present study, it can be concluded that the toxic effect of Al in the presence of acid was enhanced, whereas its toxicity was greatly reduced in the presence of the antioxidants such as omega.